Zelkovaphis trinacriae, a new Eriosomatine aphid genus and species living on Zelkova in Sicily (Rhynchota: Aphididae) (Bollettino di zoologia agraria e bachicoltura, 2024)
A new Eriosomatine aphid (Zelkovaphis trinacriae gen. n., sp. n.) livingon Zelkova sicula in Sicily is described. To the same genus are tentatively referredthe W-Asiatic Schizoneura caucasica Dzhibladze, living on Z. carpinifolia inCaucasus, and the E-Asiatic Hemipodaphis persimilis Akimoto, living on Z.serrata in Japan; a key is given to separate al ate emigrants of the three aphidspecies. A taxonomical and morphological account is given of the new genus,focussing on its relationships with other Eriosomatinae genera. Adult morphs ofZ. trinacriae on primary host and first instar nymphs of fundatrix and exules aredescribed, and notes are added on its open, leaf-roll gall and biological behaviour.The aphid secondary host plant is hitherto unknown.
Keywords: Homoptera Aphididae; Zelkovaphis trinacriae gen. n. sp. n.; Sicily